COSMOS: Computational Shaping and Modeling of Musical Structures - Chew, Elaine (Frontiers in Psychology, 2022)
Music performance is considered by many to be one of the most breathtaking feats of human intelligence. It is well accepted that music performance is a creative act, but the nature of its work remains elusive. Taking the view of performance as an act of creative problem solving, ideas in citizen science and data science, optimization, and computational thinking provide means through which to deconstruct the process of music performance. The tools offer ways to parse a musical sequence into coherent structures, to design a performance, and to explore the space of possible interpretations of the musical sequence. These ideas and tools can also be applied to other music-like sequences such as electrocardiographic recordings of arrhythmias (abnormal heart rhythms) to stratify heart rhythm disorders and characterise individual experiences of arrhythmias.